Washington Irving Chambers papers - Chambers, Washington Irving, 1856-1934.
Correspondence, memoranda, logbooks, subject files, printed matter, blueprints, photographs, and other papers relating to Chambers's service in the U.S. Navy and with the Greely Relief Expedition to the Arctic in 1884 and the Nicaragua Canal survey expedition of 1884-1885. Documents his service aboard the USS Pensacola (Screw steamer) and USS Portsmouth (Sloop of war) as well as at the Naval War College (U.S.), New York Naval Shipyard, United States Naval Torpedo Station (Newport, R.I), U.S. Navy Dept. Bureau of Navigation, U.S. Navy Dept. Bureau of Ordnance, and other Navy Dept. offices. Subjects include the development and application of aviation to naval forces, flight science and procedures, balloons, dirigibles, helicopters, parachutes, ordnance, and ship construction. Correspondents include Thomas S. Baldwin, W. Starling Burgess, Glenn Hammond Curtiss, Theodore Gordon Ellyson, Eugene Ely, Louis Godard, Roy Knabenshue, Grover Loening, Glenn L. Martin, James Means, Holden Chester Richardson, John Rodgers, and John H. Towers.
Naval officer.
Collection material in English.
Described in: Washington Irving Chambers: a register of his papers in the Library of Congress (1967).
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Baldwin, Thomas S. -- Correspondence; Burgess, W. Starling -- 1878-1947 -- Correspondence; Curtiss, Glenn Hammond, -- 1878-1930 -- Correspondence; Ellyson, Theodore Gordon, -- 1885-1928 -- Correspondence; Ely, Eugene -- Correspondence; Godard, Louis, -- 1847-1928 -- Correspondence; Greely, A. W. -- 1844-1935.; Knabenshue, Roy, -- -1960 -- Correspondence; Loening, Grover, -- 1888-1976 -- Correspondence; Martin, Glenn L. -- 1886-1955 -- Correspondence; Means, James, -- 1853-1920 -- Correspondence; Richardson, Holden Chester, -- 1878- -- Correspondence; Rodgers, John, -- 1881-1926 -- Correspondence; Towers, John H. -- 1885-1955 -- Correspondence; United States. -- Navy -- Aviation; United States. -- Navy Department; United States. -- Navy Department. -- Bureau of Navigation; United States. -- Navy Department. -- Bureau of Ordnance; Naval War College (U.S.); New York Naval Shipyard; Pensacola (Screw steamer); Portsmouth (Sloop of war); United States Naval Torpedo Station (Newport, R.I); Aeronautics; Airships; Balloons; Canals -- Nicaragua; Flight; Fortification -- Rhode Island; Helicopters; Naval aviation -- United States; Navy-yards and naval stations -- New York (State) -- New York; Navy-yards and naval stations -- Rhode Island -- Newport; Ordnance, Naval; Parachutes; Shipbuilding; Arctic regions -- Discovery and exploration; Nicaragua -- Discovery and exploration; Nicaragua Canal (Nicaragua); Naval officers